STK35 Is Ubiquitinated by NEDD4L and Promotes Glycolysis and Inhibits Apoptosis Through Regulating the AKT Signaling Pathway, Influencing Chemoresistance of Colorectal Cancer - Yang, Haojun; Zhu, Jie; Wang, Guangyao; Liu, Hanyang; Zhou, Yan; Qian, Jun (Frontiers in Cell and Developmental Biology, 2020)
The development of colorectal cancer (CRC) is often sporadic, but its etiology is multifactorial. Chemoresistance of CRC leads to tumor recurrence and poor prognosis in patients. The phosphorylation of protein kinase B (AKT) can activate metabolic reprogramming towards cellular glycolysis. Serine/threonine kinase 35 (STK35) regulates the cell cycle and is frequently associated with cancer progression, whereas little is known about its specific roles in CRC. In the current study, bioinformatics analyses were performed to investigate the relationship between STK35 and CRC prognosis. STK35 knockdown and overexpressing CRC cells were established to examine its functions in CRC. Fluorouracil (5-FU) was utilized to evaluate the effect of STK35 on CRC chemoresistance. Moreover, co-immunoprecipitation was performed to explore the ubiquitination of STK35. STK35 was highly expressed in CRC, and its protein expression was negatively correlated with the survival of CRC patients. Furthermore, STK35 overexpression could promote glycolysis, suppress apoptosis, upregulate p-AKT, and counteract the anti-tumor functions of 5-FU and neural precursor cell expressed developmentally downregulated gene 4-like (NEDD4L) in CRC cells. NEDD4L was associated with, and could ubiquitinate STK35. STK35 could be a prognostic biomarker for CRC prognosis, and has promotive effects on CRC cellular activities, partially through the AKT pathway. Moreover, STK35 also interferes with the chemosensitivity of CRC.